Crosslinkable olefin / silane interpolymer compositions having reduced peroxide levels

The process of using olefin/silane interpolymers with specific molar ratios addresses the limitations of peroxide-initiated crosslinking in olefinic polymers, achieving faster and more efficient crosslinking with reduced peroxide use, minimizing by-products, and enhancing polymer performance.

JP2024546888AActive Publication Date: 2024-12-26DOW GLOBAL TECHNOLOGIES LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024535643
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-17
Publication Date
2024-12-26
Estimated Expiration
2041-12-17

AI Technical Summary

Technical Problem

Existing peroxide-initiated crosslinking processes for olefinic polymers face challenges in achieving high cure levels while minimizing peroxide use, leading to undesirable by-products that affect odor and electrical properties, and the ratio of peroxide to coagent is limited, restricting flexibility in formulation.

Method used

A process involving olefin/silane interpolymers with Si-H groups, peroxide, and a crosslinking coagent, with a specific molar ratio of active oxygen atoms to carbon-carbon double bonds (0.02 to 0.7), allowing for reduced peroxide loading and improved cure effectiveness, reducing by-products, and enhancing curing rates.

Benefits of technology

The process enables faster crosslinking with lower peroxide use, reducing cycle times, equipment costs, and undesirable side reactions, while maintaining high cure levels and improving polymer network microstructures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546888000001
    Figure 2024546888000001
  • Figure 2024546888000002
    Figure 2024546888000002
  • Figure 2024546888000003
    Figure 2024546888000003
Patent Text Reader

Abstract

A process for forming a crosslinked composition comprising heat treating a composition comprising the following components: a) at least one olefin / silane interpolymer comprising at least one Si-H group, b) at least one peroxide, and c) at least one crosslinking coagent, wherein the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 to 0.7, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c. A process for forming a crosslinked composition comprising the following components: a) at least one olefin / silane interpolymer comprising at least one Si-H group, b) at least one peroxide, and c) at least one crosslinking coagent, wherein the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 to 0.7, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Peroxide-initiated crosslinking, functionalization, and rheology modification of polyolefin elastomers (POE) are widely used in olefin-based polymer applications. Reaction characteristics (efficiency, cure rate, and reaction selectivity) are critical factors that can greatly affect polymer formulation, part processability, and part performance. For example, olefin-based polymers with improved crosslinking speed and effectiveness can help customers reduce part manufacturing cycle times and / or minimize the usage of expensive curing additives in the formulation. There is a need for olefin-based polymer compositions that can be crosslinked with improved (faster) crosslinking speed and improved crosslinking efficiency (higher crosslinking degree). However, in peroxide-initiated crosslinking, various by-products are formed by peroxides during thermal decomposition. Such by-products in the crosslinked parts can result in undesirable properties such as unpleasant or unhealthy odors and poor electrical properties.

[0002] A crosslinking coagent is usually combined with a peroxide for crosslinking (curing). When a certain level of coagent is used, the peroxide loading can be reduced to a certain extent. By replacing a portion of the peroxide with a certain amount of coagent, the coagent can accelerate the cure without forming by-products, and thus the undesirable properties mentioned above can be mitigated. However, in conventional POE, the ratio of peroxide to coagent can only be adjusted within a narrow range without sacrificing the cure level. If a combination of too little peroxide and too much coagent (peroxide to coagent ratio is too low) is used, the desired high cure level cannot be achieved. A solution is needed to further reduce the peroxide loading level while still achieving a high cure level. This need has been met by the following inventions. Summary of the Invention

[0003] 1. A process for forming a crosslinked composition comprising the following components: a) at least one olefin / silane interpolymer containing at least one Si—H group; b) at least one peroxide, and c) at least one crosslinking coagent; the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or greater and 0.7 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0004] Ingredients include: a) at least one olefin / silane interpolymer containing at least one Si—H group; b) at least one peroxide, and c) at least one crosslinking coagent, A composition having a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or greater and 0.7 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0005] Compositions containing olefin / silane interpolymers have been found to provide the following distinguishing features and associated benefits: a) improved cure effectiveness at low peroxide loadings, thereby enabling reduced peroxide loadings, resulting in cost savings and reduced peroxide side reactions and by-products; b) improved cure speed, thereby enabling reduced cycle times, increased throughput of manufactured parts, and reduced variable equipment costs; c) selective formation of chemical bonds with silicon hydride (Si-H) functional groups, thereby enabling the design of unique polymer network microstructures with tailored properties. In the present invention, it has been unexpectedly found that the compositions of the present invention allow for a much lower ratio of peroxide to crosslinking coagent (or a much higher ratio of coagent to peroxide) to reach a certain high cure level, compared to conventional POE-based compositions.

[0006] Methods for effectively curing these compositions have also become apparent. It has also been found that the silicon hydride functional groups can readily react with peroxide to form fully crosslinked interpolymers without the need for additional curing catalysts. It has also been found that even small amounts (e.g., 5.0 wt. % or less) of silane comonomers incorporated therein significantly improve the crosslinking effectiveness of the composition compared to crosslinking ethylene-based polymers using conventional crosslinking methods.

[0007] As discussed above, in a first aspect, a process for forming a crosslinked composition is provided, the process comprising: a) at least one olefin / silane interpolymer containing at least one Si—H group; b) at least one peroxide, and c) at least one crosslinking coagent; The composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or greater and 0.7 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0008] The above process may include a combination of two or more embodiments described herein. Each component a, b, and c may include a combination of two or more embodiments described herein.

[0009] In a second aspect, a composition comprising the following ingredients: a) at least one olefin / silane interpolymer containing at least one Si—H group; b) at least one peroxide, and c) at least one cross-linking coagent; The composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or greater and 0.7 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0010] The composition may comprise a combination of two or more embodiments as described herein. Each component a, b, and c may comprise a combination of two or more embodiments as described herein.

[0011] Unless otherwise specified, the following embodiments apply to both the first and second aspects of the invention.

[0012] In one embodiment, or a combination of two or more embodiments, each of which is described herein, the olefin / silane interpolymer of component a is an ethylene / silane copolymer, an ethylene / α-olefin / silane interpolymer, or an ethylene / α-olefin / silane terpolymer. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the olefin / silane interpolymer of component a is an olefin / silane interpolymer formed in the presence of a bis-biphenyl-phenoxy metal complex.

[0013] In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition comprises only one olefin / silane interpolymer, or only one ethylene / α-olefin / silane interpolymer, or only one ethylene / α-olefin / silane terpolymer for component a. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition comprises two or more olefin / silane interpolymers, or two or more ethylene / α-olefin / silane interpolymers, or two or more ethylene / α-olefin / silane terpolymers for component a.

[0014] In one embodiment, or a combination of two or more embodiments, each of which is described herein, the interpolymer of component a comprises, in polymerized form, 0.10 wt% or more, or 0.20 wt% or more, or 0.30 wt% or more, or 0.40 wt% or more, or 0.50 wt% or more, or 0.60 wt% or more, or 0.70 wt% or more, or 0.80 wt% or more, or 0.90 wt% or more, or 1.0 wt% or more, or 1.5 wt% or more of the silane, based on the weight of the interpolymer. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the interpolymer of component a comprises, in polymerized form, 40 wt% or less, or 30 wt% or less, or 20 wt% or less, or 10 wt% or less, or 8.0 wt% or less, or 6.0 wt% or less, or 4.0 wt% or less of the silane, based on the weight of the interpolymer. In one embodiment, or a combination of two or more embodiments, each described herein, the interpolymer of component a contains, in polymerized form, 5.0 wt.% or less, or 4.5 wt.% or less, or 4.0 wt.% or less, or 3.0 wt.% or less, or 2.0 wt.% or less, or 1.5 wt.% or less of silane, based on the weight of the interpolymer.

[0015] In one embodiment, or a combination of two or more embodiments, each of which is described herein, the interpolymer of component a has a molecular weight distribution (MWD=Mw / Mn) of 1.5 or more, or 1.6 or more, or 1.7 or more, or 1.8 or more, or 1.9 or more. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the interpolymer of component a has a molecular weight distribution (MWD) of 5.0 or less, or 4.5 or less, or 4.0 or less, or 3.5 or less, or 3.0 or less, or 2.9 or less, or 2.8 or less, or 2.7 or less, or 2.6 or less, or 2.5 or less, or 2.4 or less, or 2.3 or less.

[0016] In one embodiment, or a combination of two or more embodiments, each described herein, the silane is derived from a silane monomer selected from Formula 1: A-(SiBC-O) x-Si-EFH (Formula 1), wherein A is an alkenyl group, B is a hydrocarbyl group or hydrogen, C is a hydrocarbyl group or hydrogen, and B and C can be the same or different; H is hydrogen and x≧0; E is a hydrocarbyl group or hydrogen, F is a hydrocarbyl group or hydrogen, and E and F can be the same or different.

[0017] In one embodiment, or a combination of two or more embodiments, each as described herein, Formula 1 may be represented by the following compounds s1) to s16): [ka] [ka] [ka] is selected from.

[0018] In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or more, or 0.03 or more, or 0.04 or more, or 0.05 or more, or 0.06 or more, or 0.07 or more, or 0.08 or more, or 0.09 or more, or 0.1 or more, or 0.2 or more, or 0.3 or more, or 0.4 or more, or 0.5 or more, or 0.6 or more, or 0.7 or more, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.7 or less, or 0.6 or less, or 0.5 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0019] In one embodiment, or a combination of two or more embodiments, each described herein, the composition has a weight ratio of component c to component b of at least 0.7, or at least 1.0, or at least 1.4, or at least 2.0, or at least 3.0, or at least 4.0, or at least 5.0, or at least 6.0, or at least 7.0, or at least 8.0, or at least 9.0, or at least 10.0, or at least 11.0, or at least 12.0, or at least 15.0, or at least 20.0, or at least 25.0, or at least 30.0, or at least 35.0, or at least 40.0, or at least 45.0, or at least 50.0, or at least 55.0, or at least 60.0, or at least 65.0, or at least 70.0.

[0020] In one embodiment, or a combination of two or more embodiments, each described herein, the weight ratio of component c to component b is 0.7 or greater, or 1.0 or greater, or 1.4 or greater, or 2.0 or greater, or 3.0 or greater, or 4.0 or greater, or 5.0 or greater, or 6.0 or greater, or 7.0 or greater, or 8.0 or greater, or 9.0 or greater, or 10.0 or greater, or 11.0 or greater, or 12.0 or greater, or 15.0 or greater, or 20.0 or greater, or 25.0 or greater, or 30.0 or greater, or 35.0 or greater, or 40.0 or greater, or 45.0 or greater, or 50.0 or greater, or 55.0 or greater, or 60.0 or greater, or 65.0 or greater, or 70.0 or greater. In one embodiment, or a combination of two or more embodiments, each described herein, the weight ratio of component c to component b is 100.0 or less, or 90.0 or less, or 80.0 or less, or 70.0 or less, or 65.0 or less.

[0021] In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition has a weight ratio of "active oxygen atoms in component b" to component c of 0.02 or more, or 0.03 or more, or 0.04 or more, or 0.05 or more, or 0.06 or more, or 0.07 or more, or 0.08 or more, or 0.09 or more, or 0.1 or more, or 0.2 or more, or 0.3 or more, or 0.4 or more, or 0.5 or more, or 0.6 or more, or 0.7 or more. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition has a molar ratio of "active oxygen atoms in component b" to component c of 0.7 or less, or 0.6 or less, or 0.5 or less.

[0022] In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition further comprises an ethylene / α-olefin interpolymer or an ethylene / α-olefin copolymer. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition comprises only one peroxide for component b. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition comprises two or more peroxides for component b. In one embodiment, or a combination of two or more embodiments, each of which is described herein, the composition comprises two or more crosslinking coagents for component c.

[0023] In one embodiment, or a combination of two or more embodiments, each described herein, the composition is heat treated at a temperature of 120° C. or more, or 130° C. or more, or 140° C. or more, or 150° C. or more. In one embodiment, or a combination of two or more embodiments, each described herein, the composition is heat treated at a temperature of 200° C. or less, or 195° C. or less, or 190° C. or less, or 185° C. or less, or 180° C. or less.

[0024] Also provided are crosslinked compositions formed by the inventive processes described herein or from the inventive compositions described herein.

[0025] Also provided is an article comprising at least one component formed from the composition of any one embodiment or combination of two or more embodiments, each of which is described herein. In one embodiment, or combination of two or more embodiments, each of which is described herein, the article is a film. In one embodiment, or combination of two or more embodiments, each of which is described herein, the article is a solar cell module, an encapsulation film, a cable, a footwear part, an automotive part, a window profile, a tire, a tube / hose, or a roofing membrane.

[0026] Silane Monomer Silane monomer, as used herein, contains at least one (kind of) Si-H group. In one embodiment, the silane monomer is selected from Formula 1 discussed above.

[0027] Some examples of silane monomers include hexenylsilane, allylsilane, vinylsilane, octenylsilane, hexenyldimethylsilane, octenyldimethylsilane, vinyldimethylsilane, vinyldiethylsilane, vinyldi(n-butyl)silane, vinylmethyloctadecylsilane, vinyldiphenylsilane, vinyldibenzylsilane, allyldimethylsilane, allyldiethylsilane, allyldi(n-butyl)silane, allylmethyloctadecylsilane, allyldiphenylsilane, bishexenylsilane, and allyidibenzylsilane. Mixtures of the aforementioned alkenylsilanes can also be used.

[0028] More specific examples of silane monomers include the following: (5-hexenyl-dimethylsilane (HDMS), 7-octenyldimethylsilane (ODMS), allyldimethylsilane (ADMS), 3-butenyldimethylsilane, 1-(but-3-en-1-yl)-1,1,3,3-tetramethyldisiloxane (BuMMH), 1-(hex-5-en-1-yl)-1,1,3,3-tetramethyldisiloxane (HexMMH), (2-bicyclo[2.2.1]hept-5-en-2-yl)ethyl)-dimethylsilane (NorDMS), and 1-(2-bicyclo[2.2.1]hept-5-en-2-yl)ethyl)-1,1,3,3-tetramethyldisiloxane (NorMMH). Mixtures of the aforementioned alkenylsilanes may also be used.

[0029] Peroxide As mentioned above, the composition includes a peroxide. As used herein, a peroxide contains at least one oxygen-oxygen bond (OO). Peroxides include, but are not limited to, dialkyl, diaryl, dialkaryl, and diaralkyl peroxides having the same or different respective alkyl, aryl, alkaryl, and aralkyl moieties, as well as each dialkyl, diaryl, dialkaryl, or diaralkyl peroxide having the same respective alkyl, aryl, alkaryl, or aralkyl moieties.

[0030] Exemplary organic peroxides include dicumyl peroxide ("DCP"); tert-butyl peroxybenzoate; di-tert-amyl peroxide ("DTAP"); bis(t-butyl-peroxyisopropyl)benzene ("BIPB"); isopropyl cumyl t-butyl peroxide; t-butyl cumyl peroxide; di-t-butyl peroxide; 2,5-bis(t-butylperoxy)-2,5-dimethylhexane; 2,5-bis(t-butylperoxy)-2,5-dimethylhexane-3; 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane; isopropyl cumyl cumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropyl cumyl)peroxide; 1,1-di-(tert-butylperoxy)cyclohexane ("Luperox 331"); 1,1-di-(tert-amylperoxy)cyclohexane ("Luperox 531"); tert-butyl peroxyacetate ("TBPA"); tert-amyl peroxyacetate ("TAPA"); 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane ("Luperox 101"); tert-butylperoxy-2-ethylhexyl carbonate ("TBEC"); and mixtures of two or more thereof.

[0031] In one or more embodiments, the peroxide may be a cyclic peroxide. One example of a cyclic peroxide is: Formula 2 below: [ka] (wherein R1 to R6 are each independently hydrogen or an inertly substituted or unsubstituted C1 to C20 alkyl, C3 to C20 cycloalkyl, C6 to C20 aryl, C7 to C20 aralkyl, or C7 to C20 alkaryl). Representative inert substituents included in R1 to R6 are hydroxyl, C1 to C20 alkoxy, linear or branched C1 to C20 alkyl, C6 to C20 aryloxy, halogen, ester, carboxyl, nitrile, and amide. In one or more embodiments, R1 to R6 are each independently For example, lower alkyl including C1-C10 alkyl or C1-C4 alkyl.

[0032] Some cyclic peroxides are commercially available, such as 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane, for example, under the trade name TRIGONOX. Examples of cyclic peroxides include those derived from acetone, methyl amyl ketone, methyl heptyl ketone, methyl hexyl ketone, methyl propyl ketone, methyl butyl ketone, diethyl ketone, methyl ethyl ketone, methyl octyl ketone, methyl nonyl ketone, methyl decyl ketone, methyl undecyl ketone, and combinations thereof, among others. The cyclic peroxides can be used alone or in combination with each other. The peroxides can be liquid, solid, or paste.

[0033] Crosslinking agent As used herein, a "crosslinking coagent" is a compound that promotes crosslinking, for example, by helping to establish a higher concentration of reactive sites and / or by helping to reduce the chance of harmful radical side reactions. Crosslinking coagents include triallyl cyanurate (TAC), triallyl phosphate (TAP), triallyl isocyanurate (TAIC), 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane (vinyl D4), 2,4,6-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilinane (vinyl D3), 2,4,6,8,10-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilinane (vinyl D4), 2,4,6,8,10-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilinane (vinyl D5), 2,4,6,8,10-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilinane (vinyl D6), 2,4,6,8,10-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilinane (vinyl D7), 2,4,6,8,10-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilinane (vinyl D8), 2,4,6,8,10-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilinane (vinyl D9), 2,4,6,8,10-trimethyl-2,4,6-trivinyl-1,3,5,2,4,6-trioxatrisilin Pentamethyl-2,4,6,8,10-pentavinyl-1,3,5,7,9,2,4,6,8,10-pentaoxapentasilane (vinyl D5), dipentaerythritol pentaacrylate, and trimethylolpropane triacrylate, triallyl trimellitate; N,N,N',N',N'',N''-hexaallyl-1,3,5-triazine-2,4,6-triamine; triallylol toformate, pentaerythritol triallyl ether, triallyl citarate, triallyl aconitate; trimethylolpropane triacrylate; trimethylolpropane trimethyl acrylate; ethoxylated bisphenol A dimethacrylate; 1,6-hexanediol diacrylate; pentaerythritol tetraacrylate; dipentaerythritol pentaacrylate; tris(2-hydroxyethyl)isocyanurate triacrylate; propoxylated glyceryl triacrylate; polybutadiene having a 1,2-vinyl content of at least 50% by weight; trivinylcyclohexane; certain dicarbonyl species, such as 1,3-diacetylbenzene (DAB); as well as combinations of any two or more of these.

[0034] Additives The compositions of the present invention may include one or more additives, including, but not limited to, UV stabilizers, antioxidants, fillers, scorch retarders, tackifiers, waxes, compatibilizers, adhesion promoters, plasticizers (e.g., oils), blocking agents, antiblocking agents, antistatic agents, mold release agents, antiblocking additives, colorants, dyes, pigments, and combinations thereof.

[0035] definition Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.

[0036] As used herein, the term "composition" includes mixtures of materials, including compositions and reaction products and decomposition products formed from the materials of the composition. Any reaction or decomposition products are typically present in trace or residual amounts.

[0037] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing the same or different types of monomers. Thus, the generic term polymer includes the term homopolymer (used to refer to a polymer prepared from only one type of monomer, with the understanding that trace amounts of impurities may be incorporated into the polymer structure), and the term interpolymer, as defined herein below. Trace amounts of impurities, such as catalyst residues, may be incorporated into and / or within the polymer. Typically, polymers are stabilized with very small amounts ("ppm" amounts) of one or more stabilizers.

[0038] As used herein, the term "interpolymer" refers to a polymer prepared by the polymerization of at least two different types of monomers. Thus, the term interpolymer includes the term copolymer (used to refer to a polymer prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.

[0039] As used herein, the term "olefin-based polymer" refers to a polymer that contains, in polymerized form, at least 50 weight percent, or majority weight percent (based on the weight of the polymer), of an olefin, such as ethylene or propylene, and may optionally contain one or more comonomers.

[0040] As used herein, the term "propylene-based polymer" refers to a polymer that, in polymerized form, contains at least 50 weight percent or majority weight percent propylene (based on the weight of the polymer) and may optionally contain one or more comonomers.

[0041] As used herein, the term "ethylene-based polymer" refers to a polymer that, in polymerized form, contains at least 50 weight percent or majority weight percent ethylene (based on the weight of the polymer) and may optionally contain one or more comonomers.

[0042] As used herein, the term "ethylene / α-olefin interpolymer" refers to a random interpolymer that comprises, in polymerized form, at least 50 weight percent or a majority weight percent of ethylene and an α-olefin (based on the weight of the interpolymer).

[0043] As used herein, the term "ethylene / α-olefin copolymer" refers to a random copolymer that contains, in polymerized form, at least 50 weight percent or a majority weight percent ethylene (based on the weight of the copolymer) and an α-olefin as the only two monomer types.

[0044] As used herein, the term "olefin / silane interpolymer" refers to a random interpolymer that comprises at least 50% or majority weight percent of an olefin (based on the weight of the interpolymer) and a silane monomer in polymerized form. As used herein, the interpolymer comprises at least one Si-H group, and the phrase "at least one Si-H group" refers to the type of "Si-H" group. It is understood in the art that an interpolymer contains a number of these groups. The olefin / silane interpolymer is formed by copolymerization of at least an olefin and a silane monomer (e.g., using a bis-biphenyl-phenoxy metal complex). An example of a silane monomer is shown in Formula 1 as above.

[0045] As used herein, the term "ethylene / silane interpolymer" refers to a random interpolymer that comprises, in polymerized form, at least 50% or a majority weight percent of ethylene (based on the weight of the interpolymer) and a silane monomer. As used herein, the interpolymer includes at least one Si-H group, and the phrase "at least one Si-H group" as discussed above. The ethylene / silane interpolymer is formed by copolymerization of at least ethylene and a silane monomer.

[0046] As used herein, the term "ethylene / α-olefin / silane interpolymer" refers to a random interpolymer that contains, in polymerized form, at least 50% or a majority weight percent of ethylene (based on the weight of the interpolymer), an α-olefin, and a silane monomer. As used herein, these interpolymers contain at least one Si-H group, as discussed above. Ethylene / silane interpolymers are formed by copolymerization of at least ethylene, an α-olefin, and a silane monomer.

[0047] As used herein, the term "ethylene / α-olefin / silane terpolymer" refers to a random terpolymer that, in polymerized form, contains at least 50% or a majority weight percent of ethylene, an α-olefin, and a silane monomer as the only three monomers (based on the weight of the terpolymer). As used herein, a terpolymer contains at least one Si-H group, as discussed above. Ethylene / silane terpolymers are formed by copolymerization of ethylene, an α-olefin, and a silane monomer.

[0048] As used herein, with respect to a polymer (or interpolymer or terpolymer or copolymer), the phrase "major weight percent" refers to the amount of monomer that is present in the greatest amount in the polymer.

[0049] As used herein, the terms "hydrocarbon group," "hydrocarbyl group," and similar terms refer to chemical groups that contain only carbon and hydrogen atoms.

[0050] As used herein, the term "crosslinked composition" refers to a composition having a network structure due to the formation of chemical bonds between polymer chains, the extent of which is indicated by an increase in the "MH-ML" value as discussed herein.

[0051] As used herein with respect to compositions comprising olefin / silane interpolymers, the terms "heat treating", "thermal treatment", and similar terms refer to the application of heat to the composition. Heat can be applied by electrical means (e.g., heating coils), and / or by radiation, and / or by hot oil, and / or by mechanical shear. It should be noted that the temperature at which the heat treatment is carried out refers to the temperature of the composition (e.g., the melting temperature of the composition).

[0052] As used herein, the term "bis-biphenyl-phenoxy metal complex" refers to complexes such as those disclosed in WO 2012 / 027448. Examples of such complexes include, but are not limited to, "PE CAT1" and "PE CAT2" as found in the experimental section below. Specifically, as used herein, the term "bis-biphenyl-phenoxy metal complex" refers to a chemical structure that includes a metal or metal ion bound and / or coordinated to one or more, preferably two, biphenyl-phenoxy ligands. In one embodiment, the chemical structure includes a metal bound to two biphenyl-phenoxy ligands through an oxygen atom of each respective biphenyl-phenoxy ligand. Metal complexes are typically catalytically activated by the use of one or more cocatalysts.

[0053] For example, see formula D1 below: [ka] where M1 is a metal selected from zirconium (Zr) or hafnium (Hf) or titanium (Ti), further Zr of Hf, the metal being in the +2, +3 or +4 formal oxidation state; each X is independently selected from substituted or unsubstituted (C1-C30) hydro-carbyl, substituted or unsubstituted (C1-C30) heterohydrocarbyl, and -H, and each X is independently a monodentate or bidentate ligand; n is 0, 1, or 2, and optionally when n is 1, X can be a bidentate ligand; each of -T2- and -T3- is independently selected from -O-, -S-, -N(RN)-, and -P(RP)-; R6 and R21 are each independently -H, a substituted or unsubstituted (C1-C40) hydrocarbyl, a substituted or unsubstituted (C1-C40) heterohydrocarbyl, -Si(RC) 3 , -Ge(RC) 3 , -P(RP) 2 , -N(RN) 2, -ORC, -SRC, -NO 2 , -CN, -CF 3 , RCS(O)-, RCS(O) 2 -, (RC) 2 C=N-, RCC(O)O-, RCOC(O)-, RCC(O)N(R)-, (RC) 2 NC(O)-, halogen, a group having the formula (I), a group having the formula (II), and is selected from the group consisting of groups having the formula (III): [ka] wherein R22-26, R27-34, and R35-43 each independently represent a substituted or unsubstituted (C1-C40) hydrocarbyl, a substituted or unsubstituted (C1C40) hetero-hydrocarbyl, -Si(RC) 3 , -Ge(RC) 3 , -P(RP) 2 , -N(RN) 2 , -N=CHRC, -ORC, -SRC, -NO2, -CN, -CF 3 , RCS(O)-, RCS(O) 2 -, (RC) 2 C=N-, RCC(O)O-, RCOC(O)-, RCC(O)N(RN)-, (RC 2 is selected from NC(O)-, halogen, and -H; Each of R7 to R20 is independently a substituted or unsubstituted (C1-C40) hydrocarbyl, a substituted or unsubstituted (C1-C40) heterohydrocarbyl, -Si(RC) 3 , -Ge(RC) 3 , -P(RP) 2 , -N(RN) 2 , -N=CHRC, -ORC, -SRC, -NO 2 , -CN, -CF 3 , RCS(O)-, RCS(O) 2 -, (RC 2 is selected from C=N-, RCC(O)O-, RCOC(O)-, RCC(O)N(RN)-, (RC)NC(O)-, halogen, and -H; J4 is a substituted or unsubstituted (C1-C40) hydrocarbylene or a substituted or unsubstituted (C1-C40) heterohydrocarbylene, the substituted or unsubstituted (C1-C40) hydrocarbylene having a portion (to which J4 is bonded) including a linker skeleton of 1 to 10 carbon atoms connecting groups T2 and T3 in formula D1, or the substituted or unsubstituted (C1-C40) heterohydrocarbylene having a portion including a linker skeleton of 1 to 10 atoms connecting groups T2 and T3 in formula D1, each of the 1 to 10 atoms of the linker skeleton of 1 to 10 atoms is independently a carbon atom or a heteroatom of a heteroatom group, each heteroatom group is independently O, S, S(O), S(O) 2 , Si(RC) 2 , Ge(RC) 2 , P(RC), or N(RC), where each R is independently a substituted or unsubstituted (C1-C30) hydrocarbyl or a substituted or unsubstituted (C1-C30) heterohydrocarbyl; wherein each R, R, and the remaining R in formula D1 are independently a substituted or unsubstituted (C1-C30) hydrocarbyl, a substituted or unsubstituted (C1-C30)-heterohydrocarbyl, or -H, and the metal complex is overall charge neutral.

[0054] As used herein, with respect to the term "ratio," a value of X is understood to be X:1 (or X to 1). For example, a ratio of at least 2.0 is understood to be 2.0:1.0 (or 2.0 to 1.0).

[0055] The term "alkenyl group," as used herein, refers to an organic chemical group that contains at least one carbon-carbon double bond (C=C). In a preferred embodiment, an alkenyl group is an example of a hydrocarbon group that contains at least one carbon-carbon double bond or contains only one carbon-carbon double bond.

[0056] As used herein, the term "active oxygen atom" refers to an oxygen atom that is present as one of two covalently bonded oxygen atoms in an organic peroxide. For example, a monofunctional peroxide has two active oxygen atoms. An oxygen atom that is present in an organic peroxide but is not covalently bonded to another oxygen atom is not considered to be an active oxygen atom. As used herein, "monofunctional peroxide" refers to a peroxide that has a pair of covalently bonded oxygen atoms (e.g., has the structure ROOR). A monofunctional peroxide has two active oxygen atoms. As used herein, "bifunctional peroxide" refers to a peroxide that has two pairs of covalently bonded oxygen atoms (e.g., has the structure ROOROOR). In one embodiment, the organic peroxide is a monofunctional peroxide.

[0057] "Active oxygen atom content of component b" refers to the total moles of active oxygen atoms in component b. "Carbon-carbon double bond content of component c" refers to the total moles of carbon-carbon double bonds in component c. The following equation is a calculation of the molar ratio of active oxygen atoms to carbon-carbon double bonds based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c when the composition contains only one peroxide for component b and only one crosslinking coagent for component c. When the composition contains more than one peroxide for component b and / or more than one crosslinking coagent for component c, the same calculation is performed, except that the numerator is the sum over all peroxides and the denominator is the sum over all coagents.

number

[0058] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or not, unless stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any ensuing description any other component, step, or procedure, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically defined or listed.

[0059] List of some processes and compositions A] A process for forming a crosslinked composition comprising the following components: a) at least one olefin / silane interpolymer containing at least one Si—H group; b) at least one peroxide, and c) at least one crosslinking coagent; The composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or greater and 0.7 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0060] B] The process described in A] above, wherein the olefin / silane interpolymer of component a is an ethylene / α-olefin / silane interpolymer or an ethylene / α-olefin / silane terpolymer.

[0061] C] The process according to B] above, wherein the α-olefin of the ethylene / α-olefin / silane interpolymer or terpolymer is a C3 to C20 α-olefin, or a C3 to C10 α-olefin, or a C3 to C8 α-olefin, or one of propylene, 1-butene, 1-hexene, or 1-octene, or one of propylene, 1-butene, or 1-octene, or one of 1-butene or 1-octene, or 1-octene.

[0062] D] The process of any one of A] to C] above, wherein the interpolymer of component a contains, in polymerized form, 0.10 wt% or more, or 0.20 wt% or more, or 0.30 wt% or more, or 0.40 wt% or more, or 0.50 wt% or more, or 0.60 wt% or more, or 0.70 wt% or more, or 0.80 wt% or more, or 0.90 wt% or more, or 1.0 wt% or more, or 1.5 wt% or more of silane, based on the weight of the interpolymer.

[0063] E] The process of any one of A]-D] above, wherein the interpolymer of component a contains, in polymerized form, 40 wt.% or less, or 30 wt.% or less, or 20 wt.% or less, or 10 wt.% or less, or 8.0 wt.% or less, or 6.0 wt.% or less, or 4.0 wt.% or less of silane, based on the weight of the interpolymer.

[0064] F] The process of any one of A]-E] above, wherein the interpolymer of component a contains, in polymerized form, 5.0 wt. % or less, or 4.5 wt. % or less, or 4.0 wt. % or less, or 3.0 wt. % or less, or 2.0 wt. % or less, or 1.5 wt. % or less of silane, based on the weight of the interpolymer.

[0065] G] The process described in any one of A] to F] above, wherein the interpolymer of component a has a molecular weight distribution (MWD=Mw / Mn) of 1.5 or more, or 1.6 or more, or 1.7 or more, or 1.8 or more, or 1.9 or more.

[0066] H] The process described in any one of A] to G] above, wherein the interpolymer of component a has a molecular weight distribution MWD of 5.0 or less, or 4.5 or less, or 4.0 or less, or 3.5 or less, or 3.0 or less, or 2.9 or less, or 2.8 or less, or 2.7 or less, or 2.6 or less, or 2.5 or less, or 2.4 or less, or 2.3 or less.

[0067] I] The process of any one of A] to H] above, wherein the interpolymer of component a has a number average molecular weight (Mn) of 10,000 g / mol or more, or 12,000 g / mol or more, or 14,000 g / mol or more, or 16,000 g / mol or more, or 18,000 g / mol or more, or 20,000 g / mol or more, or 22,000 g / mol or more, or 24,000 g / mol or more, or 26,000 g / mol or more, or 28,000 g / mol or more, or 30,000 g / mol or more, or 32,000 g / mol or more.

[0068] J] The process of any one of A]-I] above, wherein the interpolymer of component a has a number average molecular weight (Mn) of 100,000 g / mole or less, or 95,000 g / mole or less, or 90,000 g / mole or less, or 85,000 g / mole or less, or 80,000 g / mole or less, or 75,000 g / mole or less, or 70,000 g / mole or less, or 68,000 g / mole or less, or 66,000 g / mole or less, or 64,000 g / mole or less, or 62,000 g / mole or less, or 60,000 g / mole or less.

[0069] K] The process of any one of A]-J] above, wherein the interpolymer of component a has a weight average molecular weight (Mw) of 20,000 g / mol or more, or 25,000 g / mol or more, or 30,000 g / mol or more, or 35,000 g / mol or more, or 40,000 g / mol or more, or 45,000 g / mol or more, or 50,000 g / mol or more, or 52,000 g / mol or more, or 54,000 g / mol or more, or 56,000 g / mol or more, or 58,000 g / mol or more, or 60,000 g / mol or more, or 62,000 g / mol or more.

[0070] L] The process of any one of A]-K] above, wherein the interpolymer of component a has a weight average molecular weight (Mw) of 300,000 g / mole or less, or 250,000 g / mole or less, or 200,000 g / mole or less, or 190,000 g / mole or less, or 180,000 g / mole or less, or 170,000 g / mole or less, or 160,000 g / mole or less, or 150,000 g / mole or less, or 148,000 g / mole or less, or 146,000 g / mole or less, or 144,000 g / mole or less, or 142,000 g / mole or less, or 140,000 g / mole or less, or 138,000 g / mole or less.

[0071] M] The interpolymer of component a has a viscosity of 0.855 g / cc or more, or 0.856 g / cc or more, or 0.857 g / cc or more, or 0.858 g / cc or more, or 0.859 g / cc or more, or 0.860 g / cc or more, or 0.861 g / cc or more, or 0.862 g / cc or more, or 0.863 g / cc or more, or 0.864 g / cc or more, or 0.865 g / cc or more, or 0.866 g / cc or more, or 0.867 g / cc or more, or 0.870 g / cc or more, or 0.874 g / cc or more, or 0.876 g / cc or more, or 0.878 g / cc or more (1 cc = 1 cm 3 The process according to any one of A] to L] above, wherein the density of the resulting product is 0.01 to 0.15% by weight.

[0072] N] The interpolymer of component a has a density of 0.950 g / cc or less, or 0.920 g / cc or less, or 0.900 g / cc or less, or 0.890 g / cc or less, or 0.888 g / cc or less, or 0.886 g / cc or less, or 0.884 g / cc or less, or 0.882 g / cc or less, or 0.880 g / cc or less. The process described in any one of A] to M] above.

[0073] O] The process described in any one of A] to N] above, wherein the interpolymer of component a has a melt index (I2) of 0.5 dg / min or more, or 1.0 dg / min or more, or 2.0 dg / min or more, or 5.0 dg / min or more, or 10 dg / min or more, or 15 dg / min or more.

[0074] P] The process described in any one of A] to O] above, wherein the interpolymer of component a has a melt index (I2) of 1,000 dg / min or less, or 500 dg / min or less, or 250 dg / min or less, or 100 dg / min or less, or 50 dg / min or less, or 20 dg / min or less.

[0075] Q] The process described in any one of A] to P] above, wherein the interpolymer of component a has an I10 / I2 ratio of 6.0 or more, or 7.0 or more, or 8.0 or more, or 9.0 or more, or 10 or more.

[0076] R] The process described in any one of A] to Q] above, wherein the interpolymer of component a has an I10 / I2 ratio of 30 or less, or 25 or less, or 20 or less, or 15 or less, or 12 or less.

[0077] The process described in any one of A] to R] above, wherein S] the silane is derived from a silane monomer selected from Formula 1 described above.

[0078] T] The process described in S] above, wherein for formula 1, x is 0 to 10, or 0 to 8, or 0 to 6, or 0 to 4, or 0 to 2, or 0 or 1, or 0.

[0079] U] The process according to the above S] or T], wherein in formula 1, A is a C2 to C50 alkenyl group, or a C2 to C40 alkenyl group, or a C2 to C30 alkenyl group, or a C2 to C20 alkenyl group.

[0080] V] With respect to formula 1, A is one of the following structures i) to iv): i)R 1 R 2 C=CR 3-(In the formula, R 1 , R 2 are each independently a hydrogen atom or an alkyl group; R 3 is hydrogen and R 1 and R 2 may be the same or different), ii) R 1 R 2 C=CR 3 -(CR 4 R 5 ) n -(In the formula, R 1 , R 2 , R 4 , R 5 are each independently a hydrogen atom or an alkyl group; R 3 is hydrogen and R 1 , R 2 , R 4 , R 5 two or more of may be the same or different, and n is 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 2, or 1; iii) [ka] (In the formula, R 1 and R 2 is independently hydrogen or an alkyl group, and R 1 and R 2 may be the same or different, and n is 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 2, or 1; or iv) [ka] (In the formula, R 1 and R 2 is independently hydrogen or an alkyl group, and R 1 and R 2 may be the same or different, and n is 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 2, or 1.

[0081] W] With respect to Formula 1, A is one of the following structures i) to iv): i)H 2 C=CH- ii) H 2 C=CH-(CH 2 ) n - (wherein n is 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 2, or 1), iii) [ka] (wherein n is 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 2, or 1), or iv) [ka] (wherein n is 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 2, or 1),

[0082] X] The process according to any one of the above S] to W], wherein for formula 1, B is alkyl, or C1 to C5 alkyl, or C1 to C4 alkyl, or C1 to C3 alkyl, or C1 to C2 alkyl, or methyl.

[0083] The process according to any one of the above S] to X], wherein for formula 1, C is alkyl, or C1 to C5 alkyl, or C1 to C4 alkyl, or C1 to C3 alkyl, or C1 to C2 alkyl, or methyl.

[0084] Z] The process according to any one of the above S] to Y], wherein for formula 1, E is alkyl, or C1 to C5 alkyl, or C1 to C4 alkyl, or C1 to C3 alkyl, or C1 to C2 alkyl, or methyl.

[0085] A2] The process according to any one of the above S] to Z], wherein, for formula 1, F is alkyl, or C1 to C5 alkyl, or C1 to C4 alkyl, or C1 to C3 alkyl, or C1 to C2 alkyl, or methyl.

[0086] B2] The process according to any one of S] to A2] above, wherein formula 1 is selected from compounds s1) to s16) described above.

[0087] C2] The process according to any one of S] to B2] above, wherein formula 1 is selected from structures s1) to s8) described above.

[0088] D2] The process described in any one of S] to B2] above, wherein formula 1 is selected from structures s9) to s16) described above.

[0089] E2] Silane is the following compound: (5-hexenyl-dimethylsilane (HDMS), 7-octenyldimethylsilane (ODMS), allyldimethylsilane, 3-butenyldimethylsilane, 1-(but-3-en-1-yl)-1,1,3,3-tetramethyl-disiloxane (BuMMH), 1-(hex-5-en-1-yl)-1,1, The process according to any one of A] to D2] above, wherein the silane monomer is selected from 3,3-tetramethyldisiloxane (HexMMH), (2-bicyclo-[2.2.1]hept-5-en-2-yl)ethyl)dimethyl-silane (NorDMS), 1-(2-bicyclo[2.2.1]hept-5-en-2-yl)ethyl)-1,1,3,3-tetramethyldisiloxane (NorMMH), or any combination thereof.

[0090] F2] the composition comprises: The process of any one of A] to E2] above, having a weight ratio of component a to component b of 100 or more, or 200 or more, or 300 or more, or 400 or more, or 500 or more, or 600 or more, or 700 or more, or 800 or more, or 900 or more, or 1000 or more, or 1100 or more, or 1200 or more, or 1300 or more, or 1400 or more, or 1500 or more, or 1600 or more, or 1700 or more, or 1800 or more, or 1900 or more, or 2000 or more.

[0091] G2] the composition The process of any one of A] to F2] above, having a weight ratio of component a to component b of 3000 or less, or 2500 or less, or 2000 or less.

[0092] H2] The process of any one of A] to G2] above, wherein the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or more, or 0.03 or more, or 0.04 or more, or 0.05 or more, or 0.06 or more, or 0.07 or more, or 0.08 or more, or 0.09 or more, or 0.1 or more, or 0.2 or more, or 0.3 or more, or 0.4 or more, or 0.5 or more, or 0.6 or more, or 0.7 or more, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0093] I2] The process described in H2] above, wherein the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.7 or less, or 0.6 or less, or 0.5 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0094] J2] The process of H2] or I2] above, wherein the composition has a weight ratio of component c to component b of ≧0.7, or ≧1.0, or ≧1.4, or ≧2.0, or ≧3.0, or ≧4.0, or ≧5.0, or ≧6.0, or ≧7.0, or ≧8.0, or ≧9.0, or ≧10.0, or ≧11.0, or ≧12.0, or ≧15.0, or ≧20.0, or ≧25.0, or ≧30.0, or ≧35.0, or ≧40.0, or ≧45.0, or ≧50.0, or ≧55.0, or ≧60.0, or ≧65.0, or ≧70.0.

[0095] K2] The process of any one of A]-J2] above, wherein the composition has a weight ratio of component c to component b of 100.0 or less, or 90.0 or less, or 80.0 or less, or 70.0 or less, or 65.0 or less.

[0096] L2] The process described in any one of A] to K2] above, wherein the composition has a molar ratio of "active oxygen atoms in component b" to component c of 0.02 or more, or 0.03 or more, or 0.04 or more, or 0.05 or more, or 0.06 or more, or 0.07 or more, or 0.08 or more, or 0.09 or more, or 0.1 or more, or 0.2 or more, or 0.3 or more, or 0.4 or more, or 0.5 or more, or 0.6 or more, or 0.7 or more.

[0097] M2] The process described in any one of H2] to L2] above, wherein the composition has a molar ratio of "active oxygen atoms in component b" to component c of 0.7 or less, or 0.6 or less, or 0.5 or less.

[0098] N2] The process described in any one of H2] to M2] above, wherein the olefin / silane interpolymer of component a is an olefin / silane interpolymer formed in the presence of a bis-biphenyl-phenoxy metal complex.

[0099] O2] The process described in any one of A] to N2] above, wherein the composition comprises, based on the weight of the composition, 20.0 wt% or more, or 30.0 wt% or more, or 40.0 wt% or more, or 45.0 wt% or more, or 50.0 wt% or more, or 55.0 wt% or more, or 60.0 wt% or more, or 65.0 wt% or more, or 70.0 wt% or more, or 75.0 wt% or more, or 80.0 wt% or more, or 85.0 wt% or more, or 90.0 wt% or more, or 95.0 wt% or more, or 96.0 wt% or more, or 97.0 wt% or more, or 98.0 wt% or more, or 99.0 wt% or more of component a.

[0100] P2] The process of any one of A] to O2] above, wherein the composition comprises, based on the weight of the composition, 99.9% by weight or less, or 99.8% by weight or less, or 99.6% by weight or less, or 99.4% by weight or less, or 99.2% by weight or less, or 99.0% by weight or less, or 95.0% by weight or less, or 90.0% by weight or less, or 85.0% by weight or less, or 80.0% by weight or less, or 75.0% by weight or less, or 70.0% by weight or less, or 65.0% by weight or less, or 60.0% by weight or less, or 55.0% by weight or less, or 50.0% by weight or less of component a.

[0101] Q2] The process described in any one of A] to P2] above, wherein the composition comprises, based on the weight of the composition, 0.01 wt.% or more, or 0.05 wt.% or more, or 0.10 wt.% or more, or 0.15 wt.% or more, or 0.20 wt.% or more, or 0.30 wt.% or more, or 0.40 wt.% or more, or 0.50 wt.% or more, or 0.60 wt.% or more, or 0.70 wt.% or more, or 0.80 wt.% or more, or 0.90 wt.% or more, or 1.0 wt.% or more of component b.

[0102] R2] The process described in any one of A] to Q2] above, wherein the composition contains 5.0 wt. % or less, or 4.0 wt. % or less, or 3.0 wt. % or less, or 2.0 wt. % or less, or 1.50 wt. % or less, or 1.0 wt. % or less of component b, based on the weight of the composition.

[0103] S2] The process of any one of A] to R2] above, wherein the composition comprises at least 0.1 wt.%, or at least 0.5 wt.%, or at least 0.9 wt.%, or at least 1.00 wt.%, or at least 1.50 wt.%, or at least 1.70 wt.%, or at least 1.90 wt.%, or at least 2.0 wt.%, or at least 2.50 wt.%, or at least 3.0 wt.%, or at least 3.14 wt.%, or at least 3.15 wt.%, or at least 3.20 wt.% of component c, based on the weight of the composition.

[0104] T2] The process described in any one of A] to S2] above, wherein the composition contains 5.0 wt. % or less, or 4.0 wt. % or less, or 3.50 wt. % or less, or 3.20 wt. % or less, or 3.14 wt. % or less of component c, based on the weight of the composition.

[0105] U2] The process described in any one of A] to T2] above, wherein the composition comprises, based on the weight of the composition, 20.0 wt.% or more, or 30.0 wt.% or more, or 40.0 wt.% or more, or 50.0 wt.% or more, or 60.0 wt.% or more, or 70.0 wt.% or more, or 80.0 wt.% or more, or 90.0 wt.% or more, or 95.0 wt.% or more, or 97.0 wt.% or more, or 98.0 wt.% or more, or 98.2 wt.% or more, or 98.4 wt.% or more, or 98.6 wt.% or more, or 98.8 wt.% or more, or 99.0 wt.% or more of the sum of components a and b.

[0106] V2] The process of any one of A] to U2] above, wherein the composition comprises, based on the weight of the composition, 100.0% by weight or less, or 99.0% by weight or less, or 99.8% by weight or less, or 99.6% by weight or less, or 99.4% by weight or less, or 99.0% by weight or less, or 95.0% by weight or less, or 90.0% by weight or less, or 85.0% by weight or less, or 80.0% by weight or less, or 75.0% by weight or less, or 70.0% by weight or less, or 65.0% by weight or less, or 60.0% by weight or less, or 55.0% by weight or less, or 50.0% by weight or less of the sum of components a and b.

[0107] W2] The process of any one of A] to V2] above, wherein the composition comprises, based on the weight of the composition, 20.0 wt.% or more, or 30.0 wt.% or more, or 40.0 wt.% or more, or 50.0 wt.% or more, or 60.0 wt.% or more, or 70.0 wt.% or more, or 80.0 wt.% or more, or 90.0 wt.% or more, or 95.0 wt.% or more, or 98.0 wt.% or more, or 98.5 wt.% or more, or 99.0 wt.% or more, or 99.2 wt.% or more, or 99.3 wt.% or more, or 99.4 wt.% or more of the total of components a, b, and c, based on the weight of the composition.

[0108] X2] The process described in any one of A] to W2] above, wherein the composition comprises, based on the weight of the composition, 100.0% by weight or less, or 99.9% by weight or less, or 99.8% by weight or less, or 99.7% by weight or less, or 99.6% by weight or less, or 99.0% by weight or less, or 95.0% by weight or less, or 90.0% by weight or less, or 85.0% by weight or less, or 80.0% by weight or less, or 75.0% by weight or less, or 70.0% by weight or less, or 65.0% by weight or less, or 60.0% by weight or less, or 55.0% by weight or less, or 50.0% by weight or less of the total of components a, b, and c.

[0109] Y2] The process according to any one of A] to X2] above, wherein the composition is heat treated at a temperature of 120°C or more, or 125°C or more, or 130°C or more, or 135°C or more, or 140°C or more, or 145°C or more, or 150°C or more to 200°C or less, or 195°C or less, or 190°C or less, or 185°C or less, or 180°C or less.

[0110] Z2] The process described in any one of A] to Y2] above, wherein component c is selected from the group consisting of triallyl isocyanurate (TAIC), 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane (vinyl D4), and combinations thereof.

[0111] A3] The process of any one of A] to Z2] above, wherein the composition has an "MH-ML" value of 1.0 or more, or 1.5 or more, or 2.0 or more, or 2.5 or more, or 3.0 or more, or 3.5 or more, or 4.0 or more, or 4.5 or more, or 5.0 or more, or 5.5 or more, or 6.0 or more, or 6.5 or more, or 6.7 or more, or 7.0 or more, or 7.5 or more, or 8.0 or more, or 9.0 or more, or 10.0 or more, or 10.5 or more after heat treatment at a temperature of 150°C to 180°C for 15 to 25 minutes. The units are dN*m. The MH and ML values ​​are determined by MDR as described herein.

[0112] B3] The composition, The process according to any one of A] to A3] above, having an "MH-ML" value of 50.0 or less, or 45.0 or less, or 40.0 or less, or 35.0 or less, or 30.0 or less, or 25.0 or less, or 20.0 or less, or 15.0 or less, or 14.0 or less, or 13.0 or less, or 12.0 or less, or 11.0 or less, or 10.5 or less, or 10.0 or less, or 9.5 or less, or 9.0 or less, or 8.5 or less, or 8.0 or less, or 7.5 or less, or 7.0 or less, or 6.8 or less after heat treatment at a temperature of 150°C to 180°C for 15 to 25 minutes, in units of dN*m.

[0113] C3] The process according to any one of A] to B3] above, wherein the composition has a [(MH-ML) / T90] value of 0.10 dN*m / min or more, or 0.20 dN*m / min or more, or 0.30 dN*m / min or more, or 0.40 dN*m / min or more, or 0.50 dN*m / min or more, or 0.60 dN*m / min or more, or 0.70 dN*m / min or more, or 0.80 dN*m / min or more, or 0.90 dN*m / min or more, or 1.00 dN*m / min or more, or 1.50 dN*m / min or more, or 2.00 dN*m / min or more, or 2.50 dN*m / min or more, or 3.00 dN*m / min or more after heat treatment at a temperature of 150°C to 180°C for 15 to 25 minutes. The MH, ML, and T90 values ​​are determined by the MDR as described herein.

[0114] D3] The process of any one of A] to C3] above, wherein the composition has a [(MH-ML) / T90] value of 20 dN*m / min or less, or 18 dN*m / min or less, or 16 dN*m / min or less, or 14 dN*m / min or less, or 12 dN*m / min or less, or 10 dN*m / min or less, or 8.0 dN*m / min or less, or 6.0 dN*m / min or less, or 4.0 dN*m / min or less, or 3.0 dN*m / min or less, or 2.54 dN*m / min or less after heat treatment at a temperature of 150°C to 180°C for 15 to 25 minutes.

[0115] E3] The process according to any one of A] to D3] above, wherein the composition further comprises a thermoplastic polymer different from the interpolymer of component a in one or more characteristics, e.g., type and / or amount of monomer, density, melt index (I2), Mn, Mw, MWD, or any combination thereof, and further in one or more characteristics, e.g., type and / or amount of monomer, Mn, Mw, MWD, or any combination thereof.

[0116] F3] The process described in any one of A] to E3] above, wherein the composition further comprises an ethylene / α-olefin interpolymer or an ethylene / α-olefin copolymer.

[0117] G3] The process according to F3] above, wherein the α-olefin of the ethylene / α-olefin interpolymer or copolymer is a C3 to C20 α-olefin, or a C3 to C10 α-olefin, or a C3 to C8 α-olefin, or one of propylene, 1-butene, 1-hexene, or 1-octene, or one of propylene, 1-butene, or 1-octene, or one of 1-butene or 1-octene, or 1-octene.

[0118] H3] The olefin / silane interpolymer of component a has a melting temperature (T mThe process according to any one of A] to G3] above,

[0119] I3] The olefin / silane interpolymer of component a has a melting temperature (T m The process according to any one of A] to H3] above,

[0120] J3] The process described in any one of A] to I3] above, wherein the composition further comprises a filler and / or an oil.

[0121] K3] The process of any one of A]-J3] above, wherein the composition comprises, based on the weight of the composition, 100 ppm or less, or 50 ppm or less, or 20 ppm or less, or 10 ppm or less, or 5.0 ppm or less of Lewis acid (e.g., sulfonic acid).

[0122] L3] The process described in any one of A] to K3] above, wherein the composition does not contain a Lewis acid.

[0123] M3] The process of any one of A]-L3] above, wherein the composition comprises, based on the weight of the composition, 100 ppm or less, or 50 ppm or less, or 20 ppm or less, or 10 ppm or less, or 5.0 ppm or less of Lewis base.

[0124] N3] The process described in any one of A] to M3] above, wherein the composition does not contain a Lewis base.

[0125] O3] A crosslinked composition formed by any one of the processes A] to N3] above.

[0126] P3] An article comprising at least one component formed from the composition described in O3] above.

[0127] Q3] The article described in P3] above, wherein the article is a film.

[0128] R3] The article according to P3] above, wherein the article is a solar cell module, a cable, a footwear component, an automotive part, a window profile, a tire, a tube, or a roofing membrane.

[0129] S3] A composition comprising the following components: a) at least one olefin / silane interpolymer containing at least one Si—H group; b) at least one peroxide, and c) at least one crosslinking coagent; The composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or greater and 0.7 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0130] T3] The composition described in S3] above, wherein the olefin / silane interpolymer of component a is an ethylene / α-olefin / silane interpolymer or an ethylene / α-olefin / silane terpolymer.

[0131] U3] The composition according to T3] above, wherein the α-olefin of the olefin / silane interpolymer, or even the terpolymer, is a C3-C20 α-olefin, or a C3-C10 α-olefin, or a C3-C8 α-olefin, or one of propylene, 1-butene, 1-hexene, or 1-octene, or one of propylene, 1-butene, or 1-octene, or one of 1-butene or 1-octene, or 1-octene.

[0132] V3] The composition described in any one of S3] to U3] above, wherein the interpolymer of component a, in polymerized form, contains, based on the weight of the interpolymer, 0.10 wt.% or more, or 0.20 wt.% or more, or 0.30 wt.% or more, or 0.40 wt.% or more, or 0.50 wt.% or more, or 0.60 wt.% or more, or 0.70 wt.% or more, or 0.80 wt.% or more, or 0.90 wt.% or more, or 1.0 wt.% or more, or 1.5 wt.% or more of the silane.

[0133] W3] The composition of any one of S3] to V3] above, wherein the interpolymer of component a, in polymerized form, contains 40 wt.% or less, or 30 wt.% or less, or 20 wt.% or less, or 10 wt.% or less, or 8.0 wt.% or less, or 6.0 wt.% or less, or 4.0 wt.% or less of silane, based on the weight of the interpolymer.

[0134] X3] The composition of any one of S3]-W3] above, wherein the interpolymer of component a, in polymerized form, contains 5.0 wt.% or less, or 4.5 wt.% or less, or 4.0 wt.% or less, or 3.0 wt.% or less, or 2.0 wt.% or less, or 1.5 wt.% or less of silane, based on the weight of the interpolymer.

[0135] Y3] The composition described in any one of S3] to X3] above, wherein the interpolymer of component a has a molecular weight distribution (MWD=Mw / Mn) of 1.5 or more, or 1.6 or more, or 1.7 or more, or 1.8 or more, or 1.9 or more.

[0136] Z3] The interpolymer of component a has a molecular weight distribution MWD of 5.0 or less, or 4.5 or less, or 4.0 or less, or 3.5 or less, or 3.0 or less, or 2.9 or less, or 2.8 or less, or 2.7 or less, or 2.6 or less, or 2.5 or less, or 2.4 or less, or 2.3 or less. Compositions described in any one of S3] to Y3] above.

[0137] A4] The composition according to any one of S3] to Z3] above, wherein the interpolymer of component a has a number average molecular weight (Mn) of 10,000 g / mol or more, or 12,000 g / mol or more, or 14,000 g / mol or more, or 16,000 g / mol or more, or 18,000 g / mol or more, or 20,000 g / mol or more, or 22,000 g / mol or more, or 24,000 g / mol or more, or 26,000 g / mol or more, or 28,000 g / mol or more, or 30,000 g / mol or more, or 32,000 g / mol or more.

[0138] B4] The composition of any one of S3] to A4] above, wherein the interpolymer of component a has a number average molecular weight (Mn) of 100,000 g / mol or less, or 95,000 g / mol or less, or 90,000 g / mol or less, or 85,000 g / mol or less, or 80,000 g / mol or less, or 75,000 g / mol or less, or 70,000 g / mol or less, or 68,000 g / mol or less, or 66,000 g / mol or less, or 64,000 g / mol or less, or 62,000 g / mol or less, or 60,000 g / mol or less.

[0139] C4] The composition according to any one of S3] to B4] above, wherein the interpolymer of component a has a weight average molecular weight (Mw) of 20,000 g / mol or more, or 25,000 g / mol or more, or 30,000 g / mol or more, or 35,000 g / mol or more, or 40,000 g / mol or more, or 45,000 g / mol or more, or 50,000 g / mol or more, or 52,000 g / mol or more, or 54,000 g / mol or more, or 56,000 g / mol or more, or 58,000 g / mol or more, or 60,000 g / mol or more, or 62,000 g / mol or more.

[0140] D4] The composition of any one of S3] to C4] above, wherein the interpolymer of component a has a weight average molecular weight (Mw) of 300,000 g / mol or less, or 250,000 g / mol or less, or 200,000 g / mol or less, or 190,000 g / mol or less, or 180,000 g / mol or less, or 170,000 g / mol or less, or 160,000 g / mol or less, or 150,000 g / mol or less, or 148,000 g / mol or less, or 146,000 g / mol or less, or 144,000 g / mol or less, or 142,000 g / mol or less, or 140,000 g / mol or less, or 138,000 g / mol or less.

[0141] E4] The interpolymer of component a has a viscosity of 0.855 g / cc or more, or 0.856 g / cc or more, or 0.857 g / cc or more, or 0.858 g / cc or more, or 0.859 g / cc or more, or 0.860 g / cc or more, or 0.861 g / cc or more, or 0.862 g / cc or more, or 0.863 g / cc or more, or 0.864 g / cc or more, or 0.865 g / cc or more, or 0.866 g / cc or more, or 0.867 g / cc or more, or 0.870 g / cc or more, or 0.874 g / cc or more, or 0.876 g / cc or more, or 0.878 g / cc or more (1 cc = 1 cm 3 The composition according to any one of the above S3] to D4], having a density of

[0142] F4] The composition according to any one of S3] to E4] above, wherein the interpolymer of component a has a density of 0.950 g / cc or less, or 0.920 g / cc or less, or 0.900 g / cc or less, or 0.890 g / cc or less, or 0.888 g / cc or less, or 0.886 g / cc or less, or 0.884 g / cc or less, or 0.882 g / cc or less, or 0.880 g / cc or less.

[0143] G4] The composition described in any one of S3] to F4] above, wherein the interpolymer of component a has a melt index (I2) of 0.5 dg / min or more, or 1.0 dg / min or more, or 2.0 dg / min or more, or 5.0 dg / min or more, or 10 dg / min or more, or 15 dg / min or more.

[0144] H4] The composition according to any one of S3] to G4] above, wherein the interpolymer of component a has a melt index (I2) of 1,000 dg / min or less, or 500 dg / min or less, or 250 dg / min or less, or 100 dg / min or less, or 50 dg / min or less, or 20 dg / min or less.

[0145] I4] The composition according to any one of S3] to H4] above, wherein the interpolymer of component a has an I10 / I2 ratio of 6.0 or more, or 7.0 or more, or 8.0 or more, or 9.0 or more, or 10 or more.

[0146] J4] The composition according to any one of S3] to I4] above, wherein the interpolymer of component a has an I10 / I2 ratio of 30 or less, or 25 or less, or 20 or less, or 15 or less, or 12 or less.

[0147] K4] A composition according to any one of S3] to J4] above, wherein the silane is derived from a silane monomer selected from Formula 1 described above.

[0148] L4] The composition according to the above K4], wherein in formula 1, x is 0 to 10, or 0 to 8, or 0 to 6, or 0 to 4, or 0 to 2, or 0 or 1, or 0.

[0149] M4] The interpolymer according to the above K4] or L4], wherein in formula 1, A is a C2 to C50 alkenyl group, further a C2 to C40 alkenyl group, or a C2 to C30 alkenyl group, or a C2 to C20 alkenyl group.

[0150] N4] With respect to formula 1, A is one of the following structures i) to iv): i) R, as described above 1 R 2 C=CR 3 -; ii) R, as described above 1 R 2 C=CR 3 -(CR 4 R 5 ) n -; ii) as described above; [ka] or iv) as described above; [ka] The interpolymer according to any one of K4] to M4], wherein the interpolymer is selected from the following:

[0151] O4] With respect to Formula 1, A is one of the following structures i) to iv): i)H 2 C=CH-; ii) H, as explained above 2 C=CH-(CH 2 ) n -; iii) as described above; [ka] or iv) as described above; [ka] The interpolymer according to any one of K4] to N4], wherein the interpolymer is selected from the following:

[0152] P4] The composition according to any one of the above K4] to O4], wherein in formula 1, B is alkyl, or C1 to C5 alkyl, or C1 to C4 alkyl, or C1 to C3 alkyl, or C1 to C2 alkyl, or methyl.

[0153] Q4] The composition according to any one of the above K4] to P4], wherein in formula 1, C is alkyl, or C1 to C5 alkyl, or C1 to C4 alkyl, or C1 to C3 alkyl, or C1 to C2 alkyl, or methyl.

[0154] R4] For Eq. 1, The composition according to any one of the above K4] to Q4], wherein E is alkyl, or C1 to C5 alkyl, or C1 to C4 alkyl, or C1 to C3 alkyl, or C1 to C2 alkyl, or methyl. S4] With respect to formula 1, The composition according to any one of the above K4] to R4], wherein F is alkyl, or C1 to C5 alkyl, or C1 to C4 alkyl, or C1 to C3 alkyl, or C1 to C2 alkyl, or methyl.

[0155] T4] A composition according to any one of K4] to S4] above, wherein formula 1 is selected from compounds s1) to s16) described above.

[0156] U4] A composition according to any one of K4] to T4] above, wherein formula 1 is selected from structures s1) to s8) described above.

[0157] V4] A composition according to any one of K4] to T4] above, wherein formula 1 is selected from structures s9) to s16) described above.

[0158] W4] The composition according to any one of S3] to V4] above, wherein the silane is derived from a silane monomer selected from the following compounds: (5-hexenyl-dimethylsilane (HDMS), 7-octenyldimethylsilane (ODMS), allyldimethylsilane, 3-butenyldimethyl-silane, 1-(but-3-en-1-yl)-1,1,3,3-tetramethyl-disiloxane (BuMMH), 1-(hex-5-en-1-yl)-1,1,3,3-tetramethyldisiloxane (HexMMH), (2-bicyclo-[2.2.1]hept-5-en-2-yl)ethyl)dimethyl-silane (NorDMS) or 1-(2-bicyclo[2.2.1]hept-5-en-2-yl)ethyl)-1,1,3,3-tetramethyldisiloxane (NorMMH), and any combination thereof.

[0159] X4] A composition according to any one of S3] to W4] above, wherein the composition has a weight ratio of component b to component b of 100 or more, or 200 or more, or 300 or more, or 400 or more, or 500 or more, or 600 or more, or 700 or more, or 800 or more, or 900 or more, or 1000 or more, or 1100 or more, or 1200 or more, or 1300 or more, or 1400 or more, or 1500 or more, or 1600 or more, or 1700 or more, or 1800 or more, or 1900 or more, or 2000 or more.

[0160] Y4] The composition according to any one of S3] to X4] above, having a weight ratio of component a to component b of 3000 or less, or 2500 or less, or 2000 or less.

[0161] Z4] The composition according to any one of the above S3] to Y4], having a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or more, or 0.03 or more, or 0.04 or more, or 0.05 or more, or 0.06 or more, or 0.07 or more, or 0.08 or more, or 0.09 or more, or 0.1 or more, or 0.2 or more, or 0.3 or more, or 0.4 or more, or 0.5 or more, or 0.6 or more, or 0.7 or more, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0162] A5] The composition described in Z4] above, wherein the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.7 or less, or 0.6 or less, or 0.5 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

[0163] B5] A composition according to Z4] or A5] above, having a weight ratio of component c to component b of ≧0.7, or ≧1.0, or ≧1.4, or ≧2.0, or ≧3.0, or ≧4.0, or ≧5.0, or ≧6.0, or ≧7.0, or ≧8.0, or ≧9.0, or ≧10.0, or ≧11.0, or ≧12.0, or ≧15.0, or ≧20.0, or ≧25.0, or ≧30.0, or ≧35.0, or ≧40.0, or ≧45.0, or ≧50.0, or ≧55.0, or ≧60.0, or ≧65.0, or ≧70.0.

[0164] C5] The composition according to any one of S3] to B5] above, wherein the composition has a weight ratio of component c to component b of 100.0 or less, or 90.0 or less, or 80.0 or less, or 70.0 or less, or 65.0 or less. D5] The composition according to any one of S3] to C5] above, wherein the composition has a molar ratio of "active oxygen atoms in component b" to component c of 0.02 or more, or 0.03 or more, or 0.04 or more, or 0.05 or more, or 0.06 or more, or 0.07 or more, or 0.08 or more, or 0.09 or more, or 0.1 or more, or 0.2 or more, or 0.3 or more, or 0.4 or more, or 0.5 or more, or 0.6 or more, or 0.7 or more.

[0165] E5] The composition according to any one of Z4] to D5] above, wherein the composition has a molar ratio of "active oxygen atoms in component b" to component c of 0.7 or less, or 0.6 or less, or 0.5 or less.

[0166] F5] The composition according to any one of Z4] to E5] above, wherein the olefin / silane interpolymer of component a is an olefin / silane interpolymer formed in the presence of a bis-biphenyl-phenoxy metal complex.

[0167] G5] The composition according to any one of the above S3] to F5], comprising, based on the weight of the composition, 20.0 wt% or more, or 30.0 wt% or more, or 40.0 wt% or more, or 45.0 wt% or more, or 50.0 wt% or more, or 55.0 wt% or more, or 60.0 wt% or more, or 65.0 wt% or more, or 70.0 wt% or more, or 75.0 wt% or more, or 80.0 wt% or more, or 85.0 wt% or more, or 90.0 wt% or more, or 95.0 wt% or more, or 96.0 wt% or more, or 97.0 wt% or more, or 98.0 wt% or more, or 99.0 wt% or more of component a.

[0168] H5] A composition according to any one of S3] to G5] above, comprising, based on the weight of the composition, 99.9% by weight or less, or 99.8% by weight or less, or 99.6% by weight or less, or 99.4% by weight or less, or 99.2% by weight or less, or 99.0% by weight or less, or 95.0% by weight or less, or 90.0% by weight or less, or 85.0% by weight or less, or 80.0% by weight or less, or 75.0% by weight or less, or 70.0% by weight or less, or 65.0% by weight or less, or 60.0% by weight or less, or 55.0% by weight or less, or 50.0% by weight or less of component a.

[0169] I5] A composition according to any one of S3] to H5] above, comprising, based on the weight of the composition, 0.01 wt.% or more, or 0.05 wt.% or more, or 0.10 wt.% or more, or 0.15 wt.% or more, or 0.20 wt.% or more, or 0.30 wt.% or more, or 0.40 wt.% or more, or 0.50 wt.% or more, or 0.60 wt.% or more, or 0.70 wt.% or more, or 0.80 wt.% or more, or 0.90 wt.% or more, or 1.0 wt.% or more of component b.

[0170] J5] A composition described in any one of S3] to I5] above, comprising ≦5.0 wt.%, or ≦4.0 wt.%, or ≦3.0 wt.%, or ≦2.0 wt.%, or ≦1.50 wt.%, or ≦1.0 wt.% of component b, based on the weight of the composition.

[0171] K5] A composition according to any one of S3] to J5] above, comprising, based on the weight of the composition, 0.1 wt.% or more, or 0.5 wt.% or more, or 0.9 wt.% or more, or 1.00 wt.% or more, or 1.50 wt.% or more, or 1.70 wt.% or more, or 1.90 wt.% or more, or 2.0 wt.% or more, or 2.50 wt.% or more, or 3.0 wt.% or more, or 3.14 wt.% or more, or 3.15 wt.% or more, or 3.20 wt.% or more of component c.

[0172] L5] A composition described in any one of S3] to K5] above, comprising ≦5.0 wt.%, or ≦4.0 wt.%, or ≦3.50 wt.%, or ≦3.20 wt.%, or ≦3.14 wt.% of component c, based on the weight of the composition.

[0173] M5] The composition according to any one of S3] to L5] above, comprising, based on the weight of the composition, 20.0% by weight or more, or 30.0% by weight or more, or 40.0% by weight or more, or 50.0% by weight or more, or 60.0% by weight or more, or 70.0% by weight or more, or 80.0% by weight or more, or 90.0% by weight or more, or 95.0% by weight or more, or 97.0% by weight or more, or 98.0% by weight or more, or 98.2% by weight or more, or 98.4% by weight or more, or 98.6% by weight or more, or 98.8% by weight or more, or 99.0% by weight or more of the sum of components a and b.

[0174] N5] The composition according to any one of S3] to M5] above, wherein the composition comprises, based on the weight of the composition, 100.0% by weight or less, or 99.0% by weight or less, or 99.8% by weight or less, or 99.6% by weight or less, or 99.4% by weight or less, or 99.0% by weight or less, or 95.0% by weight or less, or 90.0% by weight or less, or 85.0% by weight or less, or 80.0% by weight or less, or 75.0% by weight or less, or 70.0% by weight or less, or 65.0% by weight or less, or 60.0% by weight or less, or 55.0% by weight or less, or 50.0% by weight or less of the sum of components a and b.

[0175] O5] The composition according to any one of S3] to N5] above, wherein the composition comprises, based on the weight of the composition, 20.0 wt % or more, or 30.0 wt % or more, or 40.0 wt % or more, or 50.0 wt % or more, or 60.0 wt % or more, or 70.0 wt % or more, or 80.0 wt % or more, or 90.0 wt % or more, or 95.0 wt % or more, or 98.0 wt % or more, or 98.5 wt % or more, or 99.0 wt % or more, or 99.2 wt % or more, or 99.3 wt % or more, or 99.4 wt % or more of the total of components a, b, and c.

[0176] P5] The composition according to any one of S3] to O5] above, wherein the composition comprises, based on the weight of the composition, 100.0% by weight or less, or 99.9% by weight or less, or 99.8% by weight or less, or 99.7% by weight or less, or 99.6% by weight or less, or 99.0% by weight or less, or 95.0% by weight or less, or 90.0% by weight or less, or 85.0% by weight or less, or 80.0% by weight or less, or 75.0% by weight or less, or 70.0% by weight or less, or 65.0% by weight or less, or 60.0% by weight or less, or 55.0% by weight or less, or 50.0% by weight or less of the total of components a, b, and c.

[0177] Q5] The composition according to any one of S3] to P5] above, wherein the composition has an "MH-ML" value of 1.0 or more, or 1.5 or more, or 2.0 or more, or 2.5 or more, or 3.0 or more, or 3.5 or more, or 4.0 or more, or 4.5 or more, or 5.0 or more, or 5.5 or more, or 6.0 or more, or 6.5 or more, or 6.7 or more, or 7.0 or more, or 7.5 or more, or 8.0 or more, or 9.0 or more, or 10.0 or more, or 10.5 or more after heat treatment at a temperature of 150°C to 180°C for 15 to 25 minutes. The units are dN*m. The MH and ML values ​​are determined by the MDR as described herein.

[0178] R5] The composition according to any one of S3] to Q5] above, wherein the composition has an "MH-ML" value of 50.0 or less, or 45.0 or less, or 40.0 or less, or 35.0 or less, or 30.0 or less, or 25.0 or less, or 20.0 or less, or 15.0 or less, or 14.0 or less, or 13.0 or less, or 12.0 or less, or 11.0 or less, or 10.5 or less, or 10.0 or less, or 9.5 or less, or 9.0 or less, or 8.5 or less, or 8.0 or less, or 7.5 or less, or 7.0 or less, or 6.8 or less after heat treatment for 15 to 25 minutes at a temperature of 150° C. to 180° C., in units of dN*m.

[0179] S5] The composition according to any one of S3] to R5] above, having a [(MH-ML) / T90] value of 0.10 dN*m / min or more, or 0.20 dN*m / min or more, or 0.30 dN*m / min or more, or 0.40 dN*m / min or more, or 0.50 dN*m / min or more, or 0.60 dN*m / min or more, or 0.70 dN*m / min or more, or 0.80 dN*m / min or more, or 0.90 dN*m / min or more, or 1.00 dN*m / min or more, or 1.50 dN*m / min or more, or 2.00 dN*m / min or more, or 2.50 dN*m / min or more, or 3.00 dN*m / min or more after heat treatment at a temperature of 150°C to 180°C for 15 to 25 minutes. The MH, ML, and T90 values ​​are determined by the MDR as described herein.

[0180] T5] The composition according to any one of S3] to S5] above, having a [(MH-ML) / T90] value of 20 dN*m / min or less, or 18 dN*m / min or less, or 16 dN*m / min or less, or 14 dN*m / min or less, or 12 dN*m / min or less, or 10 dN*m / min or less, or 8.0 dN*m / min or less, or 6.0 dN*m / min or less, or 4.0 dN*m / min or less, or 3.0 dN*m / min or less, or 2.54 dN*m / min or less after heat treatment at a temperature of 150°C to 180°C for 15 to 25 minutes.

[0181] U5] The composition according to any one of S3] to T5] above, further comprising a thermoplastic polymer different from the interpolymer of component a in one or more characteristics, such as type and / or amount of monomer, density, melt index (I2), Mn, Mw, MWD, or any combination thereof, and further in one or more characteristics, such as type and / or amount of monomer, Mn, Mw, MWD, or any combination thereof.

[0182] V5] The composition described in any one of S3] to U5] above, wherein the composition further comprises an ethylene / α-olefin interpolymer or an ethylene / α-olefin copolymer.

[0183] W5] The composition according to V5] above, wherein the α-olefin of the ethylene / α-olefin interpolymer, or even the copolymer, is a C3 to C20 α-olefin, or a C3 to C10 α-olefin, or a C3 to C8 α-olefin, or one of propylene, 1-butene, 1-hexene, or 1-octene, or one of propylene, 1-butene, or 1-octene, or one of 1-butene or 1-octene, or 1-octene.

[0184] X5] The olefin / silane interpolymer of component a has a melting temperature (T m The composition according to any one of the above S3] to W5],

[0185] Y5] The olefin / silane interpolymer of component a has a melting temperature (T m The composition according to any one of the above S3] to X5],

[0186] Z5] The composition according to any one of S3] to Y5] above, wherein the composition further comprises a filler and / or an oil.

[0187] A6] The composition according to any one of S3] to Z5] above, wherein the composition comprises, based on the weight of the composition, 100 ppm or less, or 50 ppm or less, or 20 ppm or less, or 10 ppm or less, or 5.0 ppm or less of a Lewis acid (e.g., a sulfonic acid).

[0188] B6] The composition according to any one of S3] to A6] above, wherein the composition does not contain a Lewis acid.

[0189] C6] The composition according to any one of S3] to B6] above, wherein the composition comprises, based on the weight of the composition, 100 ppm or less, or 50 ppm or less, or 20 ppm or less, or 10 ppm or less, or 5.0 ppm or less of Lewis base.

[0190] D6] The composition according to any one of S3] to C6] above, wherein the composition does not contain a Lewis base.

[0191] E6] The composition according to any one of the above S3] to D6], wherein component c is selected from the group consisting of triallyl isocyanurate (TAIC) and 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane (vinyl D4).

[0192] F6] A crosslinked composition formed from the composition described in any one of S3] to E6] above.

[0193] G6] An article comprising at least one component formed from a composition described in any one of S3] to F6] above.

[0194] H6] The article according to G6] above, wherein the article is a film.

[0195] I6] The article according to G6] above, wherein the article is a solar cell module, a cable, a footwear part, an automotive part, a window profile, a tire, a tube / hose, or a roofing membrane.

[0196] Test Method Gel Permeation Chromatography The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set at 160 degrees Celsius and the column compartment was set at 150 degrees Celsius. The columns were four AGILENT "Mixed A" 30 cm, 20 micron linear mixed bed columns. The chromatography solvent was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters and the flow rate was 1.0 milliliters / min.

[0197] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000 prepared in six "cocktail" mixtures with at least 10-fold intervals between individual molecular weights. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared in 0.025 grams in 50 milliliters of solvent for molecular weights of 1,000,000 and above, and 0.05 grams in 50 milliliters for molecular weights below 1,000,000. The polystyrene standards were dissolved at 80 degrees Celsius with gentle agitation for 30 minutes. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):

number

[0198] A fifth order polynomial was used to fit each of the polyethylene equivalent calibration points, with a small adjustment to A (approximately 0.375 to 0.445) to correct for column resolution and band broadening effects such that a linear homopolymer polyethylene standard was obtained at 120,000 Mw.

[0199] A total plate count was performed on the GPC column set using decane (prepared in TCB (0.04 g in 50 mL) and dissolved for 20 minutes with gentle stirring). Plate count (Equation 2) and symmetry (Equation 3) were measured with a 200 microliter injection according to the following equations:

number

number

[0200] Samples were prepared in a semi-automated fashion using the PolymerChar "Instrument Control" software, samples were weight-targeted at 2 mg / ml, and solvent (containing 200 ppm BHT) was added via the PolymerChar high temperature autosampler to a septa-capped vial that had been pre-sparged with nitrogen. Samples were dissolved at 160 degrees Celsius under "slow" shaking for 2 hours.

[0201] Mn (GPC) , Mw (GPC) , and Mz (GPC) The calculation was based on GPC results using the internal IR5 detector (measurement channel) of a PolymerChar GPC-IR chromatograph according to Equations 4-6 using PolymerChar GPCOne™ software, baseline-subtracted IR chromatograms at each equally spaced data collection point (i), and polyethylene equivalent molecular weights obtained from a narrow standard calibration curve for point (i) of Equation 1. Equations 4-6 are as follows:

number

number

number

[0202] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (apparent)) for each sample by aligning the RV of the respective decane peak in the sample (RV(FM sample)) with the RV of the decane peak within a narrow standard calibration (RV(FM calibrated)). Any change in time of the decane marker peak was then assumed to be related to a linear shift in flow rate (flow rate (effective)) across the run. To facilitate the highest accuracy of RV measurements of the flow marker peaks, the peaks of the flow marker concentration chromatograms were fitted to a quadratic equation using a least-squares fitting routine. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peaks, the effective flow rate (with respect to the narrow standard calibration) was calculated as Equation 7: Flow Rate (effective) = Flow Rate (apparent) x (RV (FM calibrated) / RV (FM sample)) (Equation 7). Processing of the flow marker peaks was performed via PolymerChar GPCOne™ software. An acceptable flow rate correction is one that brings the effective flow rate within ±0.7% of the apparent flow rate.

[0203] Melt Index The melt index (I2) of ethylene-based polymers is measured according to ASTM D-1238, condition 190°C / 2.16 kg (melt index (I10) is 190°C / 10.0 kg). I10 / I2 was calculated from the ratio of I10 to I2. The melt flow rate MFR of propylene-based polymers is measured according to ASTM D-1238, condition 230°C / 2.16 kg.

[0204] density ASTM D4703 was used to prepare polymer plaques for density analysis. ASTM D792, Method B was used to measure the density of each polymer.

[0205] NMR (13C and 1H) characterization of the terpolymer 13 For C NMR experiments, samples were dissolved in tetrachloroethane-d 2 (0.025M Cr(acac) 3 The tubes were dissolved in 100 mL of 5% ethanol (with or without 5% CO). The concentration was approximately 300 mg / 2.8 mL. Each tube was then heated in a heating block set at 110° C. The sample tubes were repeatedly vortexed and heated to obtain a homogenous flowing fluid. 13 C NMR spectra were obtained on a BRUKER AVANCE 600 MHz spectrometer equipped with a 10 mm C / H DUAL cryoprobe. The following acquisition parameters were used: 60 s relaxation time, 12.0 μs 90 degree pulse, 256 scans. The spectral center was 100 ppm and the spectral width was 250 ppm. All measurements were performed at 110 °C without spinning the sample. 13 C NMR spectra were referenced to 74.5 ppm for the solvent resonance peak. For samples containing Cr, data was acquired with a relaxation time of 7 seconds and 1024 scans. The octene (or other α-olefin) mole % was calculated based on the integral of the CH / CH carbons associated with octene (or other α-olefin) versus the CH associated with ethylene units.

[0206] 1 For H NMR experiments, each sample was analyzed using an 8 mm NMR tube with tetrachloroethane-d 2 (0.001M Cr(acac) 3 The tubes were dissolved in 100 mL of 5% ethanol (with or without 5% CO). The concentration was approximately 100 mg / 1.8 mL. Each tube was then heated in a heating block set at 110° C. The sample tubes were repeatedly vortexed and heated to obtain a homogenous flowing fluid. 1 H NMR spectra were obtained on a BRUKER AVANCE 600 MHz spectrometer equipped with a 10 mm C / H DUAL cryoprobe. Standard single pulse 1H NMR experiments were performed using the following acquisition parameters: 70 s relaxation time, 17.2 μs 90 degree pulse, 32 scans. The spectrum center was 1.3 ppm and the spectrum width was 20 ppm. All measurements were performed at 110 °C without sample spinning. 1 H NMR spectra were referenced to the solvent (residual protonated tetrachloroethane) resonance peak at 5.99 ppm. For samples containing Cr, data were acquired with a relaxation time of 16 seconds and 128 scans. The mole % silane (silane monomer) was calculated based on the integral of the SiMe proton resonance relative to the integral of the CH2 protons associated with the ethylene units and the CH3 protons associated with the octene units.

[0207] Moving Die Rheometer (MDR) The evaluation of peroxide reaction on olefin / silane interpolymers was evaluated by moving die rheometer test (MDR) as follows. Crosslinking properties were measured using Alpha Technologies moving die rheometer (MDR) 2000E according to ASTM D5289 at an amplitude of oscillation of 0.5 arc degrees. For each composition, the MDR was loaded with approximately 4.5 g of compounded composition (soaked or imbibed pellets, see mixing procedure below). The MDR was performed at 160°C (for TBEC) for 15 minutes, 150°C (for EnoxCH-80MO) for 25 minutes, and 180°C (for Luperox101) for 25 minutes with an oscillation frequency of 100 CPM (1.67 Hz) and an oscillation angle of 0.5 degrees (7% strain). The minimum torque (ML) and maximum torque (MH) applied by the MDR during the test interval are reported in dNm. The difference between MH and ML indicates the degree of crosslinking, the greater the difference, the greater the degree of crosslinking. The time taken for the torque to reach 90% of MH (t90) is reported in minutes. The time required for one (ts1) point increase from the minimum torque is recorded in minutes. The ts1 value indicates the time required to initiate the crosslinking process. A shorter time indicates that crosslinking begins more quickly.

[0208] Differential Scanning Calorimetry (DSC) Differential scanning calorimetry (DSC) was used to measure the T m , T c , T g , and crystallinity. Each sample (0.5 g) was compression molded into a film at 5000 psi for 2 min at 190 °C. Approximately 5-8 mg of film sample was weighed and placed into a DSC pan. A lid was crimped onto the pan to ensure a closed atmosphere. The sample pan was placed into the DSC cell and then heated at a rate of approximately 10 °C / min to a temperature of 180 °C for PE (230 °C for PP). The sample was held at this temperature for 3 min. The sample was then cooled at a rate of 10 °C / min to -60 °C for PE (-90 °C for PP) and held isothermally at that temperature for 3 min. The sample was then heated at a rate of 10 °C / min until completely melted (second heat). The melting point (T m ) and glass transition temperature (T g ) is determined from the second heating curve and is the crystallization temperature (T c ) was determined from the first cooling curve. T m and T c The peak temperatures of each of the three samples were recorded. The percent crystallinity was calculated based on the heat of fusion (H ) determined from the second heating curve. f ) by the theoretical heat of fusion of 292 J / g for PE (165 J / g for PP) and multiplying this amount by 100 (e.g., crystallinity % = (Hf / 292 J / g) x 100 for PE). m A peak is typically observed, where the T of the polymer m The highest temperature peak is recorded as the

[0209] experiment material Luperox TBEC: Peroxide available from Arkema (tert-butylperoxy 2-ethylhexyl carbonate); Luperox101: Peroxide available from Arkema (2,5-bis(tert-butylperoxy)-2,5-dimethylhexane); Enox CH-80MO: peroxide available from Chinasun Specialty Products Co., Ltd. (1,1-di-(tert-butylperoxy)cyclohexane, 80% purity); Vinyl D4: a crosslinking coagent available from The Dow Chemical Company (1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane); TAIC: Crosslinking coagent available from Farida Chemicals Co., Ltd. (triallyl isocyanurate); ENGAGE™ 8669: Polyolefin elastomer (ethylene / 1-octene copolymer) available from The Dow Chemical Company, density = 0.873 g / cm 3 (ASTM D792), I2 = 14.0 g / 10 min (ASTM D1238, at 190°C / 2.16 kg); 0 wt% SiH; SiH POE D: ethylene / octene / silane terpolymer, density = 0.873 g / cc, I2 = 0.8 g / 10 min, 1.5 wt% HDMS; SiH POE G: Ethylene / octene / silane terpolymer, density = 0.879 g / cc, I2 = 15.7 g / 10 min, 4.0 wt% HDMS; POED: Ethylene / octene copolymer, density = 0.871 g / cc, I2 = 1.2 g / 10 min, 0 wt% SiH.

[0210] Polymer Synthesis and Properties Interpolymers SiH-POE D, SiH-POE G, and POE D were each prepared in a hydraulically filled, 1-gallon polymerization reactor operated at steady-state conditions. The solvent was ISOPAR-E supplied by ExxonMobil Chemical Company. 5-Hexenyldimethylsilane (HDMS) supplied by Gelest was used as the termonomer and was purified with AZ-300 alumina supplied by UOP Honeywell prior to use. HDMS was fed to the reactor as a 22 wt.% solution in ISOPAR-E. The reactor temperature was measured at or near the reactor outlet. The interpolymers were isolated and pelletized. The polymerization conditions are listed in Tables 1B-1D, and the cocatalysts are listed in Table 1A. The polymer properties of each ethylene / octene / silane terpolymer (SiH-POE) and ethylene / octene copolymer (POE) are shown in Tables 2A and 2B. [Table 1] [Table 2] [Table 3] *"ppm" amounts based on the weight of the respective catalyst feed solution. [Table 4] *"ppm" amount based on weight of cocatalyst feed solution. **"ppm" amount of Al based on weight of cocatalyst feed solution. [Table 5] *Mole % silane based on total moles of monomer in polymer as determined by 1H NMR. **Calculated from mole %, weight % of silane based on weight of interpolymer. HDMS = 5-hexenyldimethylsilane. [Table 6]

[0211] Improved Peroxide Crosslinking of the Compositions of the Invention The polymer compositions (parts by weight per hundred resin / rubber, phr) and cure properties are listed in Tables 3-7. For each composition, the polymer resin was first soaked in a solution of peroxide and coagent in a fluorinated bottle for 24 hours on a roller at 50° C. (for Vinyl D4) and 60° C. (for TAIC). The soaked pellets were used in the MDR test described above for cure evaluation.

[0212] Inventive Examples 1-18 (IE-1-IE-18) represent inventive compositions of the present application, each of which comprises at least one olefin / silane interpolymer containing at least one Si-H group, at least one peroxide, and at least one crosslinking coagent, each of which has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or more and 0.7 or less, based on the active oxygen content of component b and the carbon-carbon double bond content of component c. In other words, each of IE-1-IE-18 has a reduced level of peroxide such that the amount of coagent is actually greater than the amount of peroxide. It is therefore surprising that each of IE-1-IE-18 can achieve a relatively high level of cure and a fast cure, despite the reduced amount of peroxide.

[0213] In contrast, as seen in Comparative Examples 1-18 (CE-1-CE-18), compositions with conventional POE (ENGAGE™ 8669 and POE D) are adversely affected by the reduced peroxide levels in that they are unable to achieve high cure levels or fast crosslinking rates compared to the inventive examples. Thus, the present application is an advance over the state of the art in that it provides a solution to further reduce peroxide loading levels while still achieving high cure levels.

Table 7

Table 8

Table 9

Table 10

Table 11

Claims

1. 1. A process for forming a crosslinked composition comprising the following components: a) at least one olefin / silane interpolymer containing at least one Si—H group; b) at least one peroxide, and c) at least one cross-linking coagent; the composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or greater and 0.7 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

2. The process of claim 1, wherein the interpolymer of component a is an ethylene / α-olefin / silane interpolymer.

3. 3. The process of claim 1 or 2, wherein the interpolymer of component a comprises, in polymerized form, 0.10 weight percent or more of the silane, based on the weight of the interpolymer.

4. The process of any one of claims 1 to 3, wherein the interpolymer of component a comprises, in polymerized form, up to 40 weight percent of the silane, based on the weight of the interpolymer.

5. The process of any one of claims 1 to 4, wherein the composition is heat treated at a temperature of 120°C or higher.

6. A crosslinked composition formed by the process of any one of claims 1 to 5.

7. Ingredients below: a) at least one olefin / silane interpolymer containing at least one Si—H group; b) at least one peroxide, and c) at least one crosslinking coagent, The composition has a molar ratio of active oxygen atoms to carbon-carbon double bonds of 0.02 or greater and 0.7 or less, based on the active oxygen atom content of component b and the carbon-carbon double bond content of component c.

8. The composition of claim 7, wherein the olefin / silane interpolymer of component a is an ethylene / α-olefin / silane interpolymer.

9. The silane is derived from a silane monomer selected from formula 1: A-(SiBC-O) x -Si-EFH (Formula 1), (Wherein A is an alkenyl group, B is a hydrocarbyl group or hydrogen, C is a hydrocarbyl group or hydrogen, B and C may be the same or different, H is hydrogen and x≧0; E is a hydrocarbyl group or hydrogen, F is a hydrocarbyl group or hydrogen, E 9. The composition of claim 7 or 8, wherein and F may be the same or different.

10. Formula 1 is the following compounds s1) to s16): 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 The composition according to any one of claims 7 to 9, selected from

11. The composition of any one of claims 7 to 10, wherein the composition has a weight ratio of component c to component b of 0.7 or greater.

12. The composition of any one of claims 7 to 11, wherein the composition has a weight ratio of component c to component b of less than or equal to 100.

0.

13. The composition of any one of claims 7 to 12, wherein the composition has a weight ratio of component a to component b of 100 or greater.

14. The composition of any one of claims 7 to 13, wherein the composition has a weight ratio of component a to component b of 3000 or less.

15. An article comprising at least one component formed from the composition of any one of claims 7 to 14.

Citation Information

Patent Citations

  • Production of crosslinked polyolefin

    JP1994271683A

  • Improved Silane Functional Group-Containing Olefin Interpolymers and Their Derivatives

    JP2003518523A

  • Filler for solar cell module

    JP2012099585A

  • Improved silane functionalized olefin interpolymers and derivatives thereof

    KR100656109B1

  • Silane functionalized olefin interpolymer derivatives

    US6624254B1